Prospects and Challenges of Renewable Energy in Ethiopia With Special Focus on Trends and Practices - Sawo, Bisrat Abera (Universitas Syiah Kuala, 2024)
This study aimed to explore the prospects and challenges of Renewable Energy in Ethiopia with a special focus on trends and practices. The study was conducted using a qualitative approach to understand the underlying problems of the topic holistically. The targets of the study included the Ministry of Water and Energy, the Ethiopian Energy Authority, the Ethiopia Water Technology Institute, and Ethiopian Solar Development Associations, which are responsible for leading the Renewable Energy sector of the country. A purposive sampling technique was used to collect data from sample respondents with rich experiences and exposure to Ethiopia's renewable energy sector's practices and trends through an in-depth interview, Focus Group Discussions (FGD), and document analysis of Renewable energy policy and strategy and Energy policy documents. The data were analyzed using thematic approaches. The findings revealed that Renewable Energy in Ethiopia has suffered from a lack of infrastructure and investment in renewable energy projects, technical and financial constraints in developing renewable energy technologies, regulatory and policy barriers, limited access to financing, and Intermittent nature of some renewable energy sources and challenges for grid integration and stability. Lack of strong and committed leadership is also a core problem in supporting the sector. Based on these findings, the researcher suggested that the leadership on renewable energy in Ethiopia needs to be characterized by a commitment to policy and regulatory framework implementations that support the sector's sustainable development. By formulating clear and supportive policies, the government seeks to create an enabling environment for renewable energy deployment, attract investment, and ensure the long-term viability of renewable energy projects. Overall, in alignment with the government's commitment to advance renewable energy concerning the country's broader development objectives and underscoring the transformative potential of clean energy in driving Ethiopia's sustainable growth and prosperity; the countrys leadership perspective on renewable energy needs to reflect a comprehensive and multifaceted approach that encompasses energy access, environmental sustainability, economic development, technological innovation, regional cooperation, affordability, and policy support.